Image‐guided lymph node core‐needle biopsy predicts survival in mycosis fungoides and Sézary syndrome. (1st March 2021) - Calvani, J.; de Masson, A.; de Margerie‐Mellon, C.; de Kerviler, É.; Ram‐Wolff, C.; Gruber, A.; Meignin, V.; Brice, P.; Sadoux, A.; Mourah, S.; Bagot, M.; Battistella, M.
Summary: Background: The prognosis of Sézary syndrome (SS) and mycosis fungoides (MF) depends on lymph node (LN) involvement. The usefulness of LN image‐guided core‐needle biopsies (CNBs), instead of surgical sampling, has been poorly evaluated. Objectives: To determine the prognostic value of LN CNB in MF/SS. Methods: A retrospective search was conducted to identify all LN biopsy specimens of MF/SS between 2008 and 2019. Biopsies were staged according to the International Society for Cutaneous Lymphomas/European Organisation for Research and Treatment of Cancer (ISCL/EORTC) criteria. We performed immunolabelling and determined the tumour clone frequency (TCF) by high‐throughput sequencing of the T‐cell receptor beta locus. Results: We included 119 consecutive biopsies from 100 patients, 45 with MF and 55 with SS. N1, N2 and N3 stages were diagnosed in 34 (29%), 26 (22%) and 59 (49%) cases, respectively. The TCF, Ki67 index, and percentage of cells positive for thymocyte selection‐associated high mobility group box protein (TOX), programmed cell death protein 1 (PD1), killer cell immunoglobulin‐like receptor 3DL2 (KIR3DL2) and cluster of differentiation (CD)30 were all positively correlated with the N stage. Median overall survival (OS) for N1/N2 vs. N3 patients was 42 months (range 26–not reached) vs. 14 months (range 5–30), respectively ( P < 0·001). In univariate analyses, an age > 75 years, LN short‐axis diameter > 15 mm, N3 stage, presence of large‐cell transformation, TOX > 60%, PD1 > 25%, Ki67 > 30%, KIR3DL2 > 15%, CD30 > 10% and TCF > 25% were identified as adverse prognostic factors. In multivariate analyses, only an age > 75 years and Ki67 index > 30% were associated with reduced OS. We developed a new prognostic index associating the N stage and the Ki67 index, which better discriminates N3 patients with poor prognosis. Conclusions: CNB allows an objective assessment of the LN involvement in MF/SS, relevant for staging and prognosis. Abstract : What is already known about this topic? The prognosis of Sézary syndrome (SS) and mycosis fungoides (MF) depends on lymph node (LN) involvement. The usefulness of LN core‐needle biopsies (CNBs) instead of surgical sampling in MF/SS has been poorly evaluated. What does this study add? LN image‐guided CNB allows objective assessment of LN involvement in MF/SS, relevant for staging and prognosis. Expression of TOX, PD1, CD30 and KIR3DL2 is correlated with ISCL/EORTC N stage and with tumour clone frequency as assessed by next‐generation high‐throughput DNA sequencing of the T‐cell receptor beta locus. Ki67 index > 30% appears as an independent factor associated with overall survival. Linked Comment: E. Hodak. Br J Dermatol 2021; 185 :251–252 . Plain language summary available online